Does the energy restriction intermittent fasting diet alleviate metabolic syndrome biomarkers? A randomized controlled trial - Ergül Kunduracı, Yasemin; Özbek, Hanefi (MDPI, 2020)
The aim of this study was to determine the efficacy of an energy restriction intermittent fasting diet in metabolic biomarkers and weight management among adults with metabolic syndrome. This randomized controlled study was performed with metabolic syndrome patients, aged 18-65 years, at an academic institution in Istanbul, Turkey (n = 70). All participants were randomized to the Intermittent Energy Restriction (IER) intervention group and Continuous Energy Restriction (CER) control group. Biochemical tests including lipid profile, fasting plasma glucose, insulin, glycosylated hemoglobin Type A1c (HbA1c), homeostatic model assessment of insulin resistance (HOMA-IR), blood pressure, and body composition were evaluated at baseline and at the 12th week in diet interviews. Dietary intake was measured with the 24-h dietary recall method and dietary quality was evaluated with the Healthy Eating Index-2010. Changes in body weight (approximate to 7% weight loss) and composition were similar in both groups. Blood pressure, total cholesterol, triglyceride, low-density lipoprotein (LDL), fasting glucose, and insulin at the 12th week decreased in both groups (p < 0.05). No significant differences were observed in metabolic syndrome biomarkers between the IER and CER groups. The energy-restricted intermittent fasting diet did not cause any deficiencies in macronutrient and fiber intake in the subjects. Healthy Eating Index (HEI) index scores were achieved similarly in both groups, and subjects' dietary intakes were close to daily reference nutritional intake values. The technique used to achieve energy restriction, whether intermittent or continuous, appears to alleviate the metabolic syndrome biomarkers activated by weight loss.
Keywords: Metabolic Syndrome; Intermittent Fasting; Energy Restriction; Weight Loss; Body Composition; Blood Pressure